Low-coverage heteroepitaxial growth with interfacial mixing. (9th January 2015) - Mazzitello, K I; Delgado, L M; Iguain, J L
Abstract: We investigate the influence of intermixing on heteroepitaxial growth dynamics, using a two-dimensional point island model, expected to be a good approximation in the early stages of epitaxy. In this model, which we explore both analytically and numerically, every deposited B atom diffuses on the surface with diffusion constant D B and can exchange with any A atom of the substrate at constant rate. There is no exchange back and emerging atoms diffuse on the surface with diffusion constant D A . When any two diffusing atoms meet, they nucleate a point island. The islands neither diffuse nor break and grow by capturing other diffusing atoms. The model leads to an island density governed by the diffusion of one of the species at low temperature and by the diffusion of the other at high temperature. We show that these limit behaviors, as well as intermediate ones, all belong to the same universality class, described by a scaling law. We also show that the island-size distribution is self-similarly described by a dynamic scaling law in the limits where only one diffusion constant is relevant to the dynamics and that this law is affected when both D A and D B play a role.